WISATA BERBASIS KOMUNITAS - Ainurrahman, Ainurrahman (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Ainurrahman (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan. mahasiswa Program Doktor Pascasarjana UGM Yogyakarta e-mail: anik_mamang@yahoo.com; 081230185895)     Abstract Unprofessional tourism village starts from a paradigm stating that a community is lack of both knowledge and skill to manage and to develop its own tourism village. Ideally, a Tourism Village must stand on the princple of community based tourism and community based culture centered. One of the parameters of professional tourism village is determined by the quality of truth and opportunity given by the local government for the community to manage and develop a tourism place. The beauty of nature, cultural tradition, and the community daily life are the three basic components in organizing and expanding a total tourism village. Kata-kata kunci komunitas, budaya, wisata